Digital Promotion in Attracting the Interest of Gen Z Consumers: A Study of the Surabaya-Ende Delivery Service Business - Angelina Venesa Keytimu; Chitra Rithmaya (Universitas Kristen Petra dan Ikatan Sarjana Ekonomi Indonesia Cabang Surabaya, 2026)
The rapid development of digital technology has significantly transformed consumer behavior, particularly among Generation Z, who are highly adaptive to social media and digital platforms. One of the emerging business sectors leveraging this trend is personal shopping services (Jastip), which rely heavily on digital promotion strategies to reach consumers across regions. However, the effectiveness of digital promotion strategies in increasing consumer interest, especially in the context of jastip businesses, remains underexplored. This study aims to analyze the effectiveness of digital promotion strategies in increasing Generation Z consumer interest in a personal shopping service business operating between Surabaya and Ende. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subject is a jastip business actively utilizing social media as its primary promotional channel. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that digital promotion strategies using social media platforms, particularly Instagram Stories and WhatsApp Stories, are effective at attracting Generation Z consumers. Visual, real-time, and interactive promotional content, such as behind-the-scenes content, customer testimonials, and batch-based ordering systems, plays a significant role in building trust and engagement. Nevertheless, several challenges were identified, including limited promotional reach, low consumer trust, logistical constraints, and rapidly changing trends among Generation Z. The implementation of appropriate digital promotion strategies has positively impacted consumer interest, as indicated by increased customer interactions and a rise in monthly revenue from approximately IDR 5–6 million to IDR 9–10 million. This study suggests that adaptive digital promotion strategies aligned with Generation Z characteristics, combined with transparency and consistency in content delivery, are crucial for enhancing the competitiveness of personal shopping service businesses in the digital era.